TINJAUAN TERHADAP BENTUK DAN MAKNA KATA SERAPAN BAHASA BELANDA DALAM BAHASA INDONESIA - Sri Wahyuni; Hasnah Faizah; Auzar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACTION: This Research study about Evaluation of form and Mean The Word of Absorption of Dutch Ianguage in Indonesian. This Research used approach qualitative having the character of descriptive which aim to for the description of vocabulary of absorption of Dutch Ianguage in this Ianguage Indonesia. Because research only limited to word collection, hence use of various certain dictionary very that dibutuhkan. Without other;dissimilar reference use also partake to support this research. Following various reference which used as a data source. Foreign absorption Words dictionary in Indonesian (J.S Badudu, 2003), dictionary of Indonesian Etymology (Department of Education And Culture Jakarta, 1987), dictionary of absorption Word (Surawan Matinus,), Absorption Element in Indonesian and its instruction (Mansoer Pateda-Yennie P. Pulubuhu, 1987), Absorption word from Ianguage Belanda / english (Sudarno,1). Result of this research represent a[n word order form absorption grouped by pursuant to form and its meaning each that is Evaluate To Form and Mean The Word of Absorption of Dutch Ianguage in Indonesian.Keywords : Word Of Absorption Of Dutch Language